Gavan Edmund Rosman (1934–2022) - Richardson, James; Ayre, Robert; Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2022)
Gavan Rosman was valued at the Telecom (later Telstra) Research Laboratories, Australia, for his expertise as a research engineer in radio and coaxial cable technologies and, in particular, for his pioneering work on optical fibre technologies. He was also valued for his wide-ranging intellect and gentle, satirical sense of humour. His fluency in speaking Japanese was appreciated by visiting Japanese researchers. In retirement from TRL, he worked at Optiscan Imaging in Melbourne on developing an optical endoscope.